Clearinghouse-Five: determinants of voluntary clearing in European derivatives markets - Paweł Fiedor (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2018)
Central clearing is a major part of the policy response to the financial crisis of 2008, aiming to reign in counterparty credit risk in derivatives markets. I perform an empirical study of the incentives for voluntary central clearing of OTC derivative contracts in Europe. Central clearing acts as insurance against counterparty credit risk related to derivative contracts, and is legally mandated for a specific subset of standardized derivative contracts, with a significant portion of the other contracts eligible for voluntary clearing. I show that there exist significant economies of scale in central clearing, in terms of both the size of each contract, and the scale of total clearing activity. I also show that maturity of the contract and international frictions affect voluntary clearing of different types of derivative contracts in different ways, linked to the conventional maturity and payout structures of various types of contracts. Finally, I show that significant amount of clearing happens only for credit and interest rate derivatives, while equity, foreign exchange, and commodity derivatives are rarely centrally cleared. The results validate theoretical literature, and guide future modeling of derivative markets.
Keywords: C58; G28; G32; 330; derivatives; central counterparties; incentives; central clearing